The deployment and internationalization speed of e-business in the digital entrepreneurship era - Babak Ziyae; Seyed Sajadi; Mohammad Mobaraki (Journal of Global Entrepreneurship Research, 2014)
Digital Entrepreneurship has revolutionized worldwide businesses. Worked by the fast development of computer knowledge, Electronic Businesses (here in after acronym as EBSs) are experiencing the increasing growth in the global economy. The purpose of this paper is to investigate the effect of entrepreneurs' international experience, innovation capability, and market capability on the internationalization speed of EBSs. The current study is considered as an empirical research and the research methodology is descriptive-correlative type. The data collected from Small and Medium-Sized Enterprises (here after acronym as SMEs) whose activities are partially internet-based and have involved in the international business processes. A total of 135SMEsin the textile cluster were classified as the internet-based businesses. To test the research hypotheses, the study used Structure Equation Modeling (SEM) and the collected data were subjected to correlational analysis and path analysis. The results revealed that the speed of foreign market entry by EBSs is positively affected by entrepreneurs' international experience, business innovation capability, and marketing capability. Finally, this study proposes insights for future studies that could consider the implications of speedy entry into foreign markets by EBSs.
Keywords: 650; Entrepreneurs' international experience; Business innovation capability; Marketing capability; internationalization speed; Digital entrepreneurship